2016
DOI: 10.1021/acs.jpcc.6b00204
|View full text |Cite
|
Sign up to set email alerts
|

Porous SiOCH Thin Films Obtained by Foaming

Abstract: Porous organosilicate thin films (SiOCH) deposited by plasma-enhanced chemical vapor deposition (PECVD) are used as dielectric layers in advanced microelectronic interconnections and as chemical layers in chemical sensors and biosensors. One challenge is to increase the porosity in these films, the classical method being limited to porosity rate close to 50%. In this paper, we report an innovative and simple strategy to perform highly nanoporous SiOCH thin films without the use of any templates or external blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…For each deposition condition (monomer and frequency), the thickness and mass growth rates were determined from the measured thicknesses and weight of a minimum of two different thin films prepared using different deposition times. The effective deposition time, which is the time effectively spent under the high-voltage electrodes and calculated independently from the plasma pulse frequency, corresponds to the number of runs (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) multiplied by the width of the high-voltage electrodes (30 mm) divided by the speed of the moving table (1-3 mm•s −1 ). For all the experiments reported in this study, the growth rates were shown to be directly proportional to the deposition time, yielding small standard deviations of the growth rates, even though they were evaluated from thin films prepared with different deposition times.…”
Section: Thin-film Characterisation 231 | Morphology and Topographymentioning
confidence: 99%
See 1 more Smart Citation
“…For each deposition condition (monomer and frequency), the thickness and mass growth rates were determined from the measured thicknesses and weight of a minimum of two different thin films prepared using different deposition times. The effective deposition time, which is the time effectively spent under the high-voltage electrodes and calculated independently from the plasma pulse frequency, corresponds to the number of runs (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) multiplied by the width of the high-voltage electrodes (30 mm) divided by the speed of the moving table (1-3 mm•s −1 ). For all the experiments reported in this study, the growth rates were shown to be directly proportional to the deposition time, yielding small standard deviations of the growth rates, even though they were evaluated from thin films prepared with different deposition times.…”
Section: Thin-film Characterisation 231 | Morphology and Topographymentioning
confidence: 99%
“…[ 5 ] Plasma‐enhanced chemical vapour deposition (PECVD) processes have been widely used for the elaboration of low‐ k thin films. [ 6,7 ] If several strategies (i.e., porogen approach, [ 8 ] foaming approach, [ 9 ] cyclic precursor approach [ 10 ] and carbon‐bridging approach [ 11 ] ) have been proposed to lower the dielectric constant of the materials, the resulting thin films, called “plasma polymers,” suffer from moderate‐to‐poor retention of the precursor structure or/and limited mechanical or insulating properties. In particular, the PECVD of low‐ k dielectric thin films from constitutive porosities (e.g., cyclic precursor approach) is restricted by the disruption of the ring structure of cyclic precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TPEEs are applied to components and lightweight seats for automobiles, outdoor products where elasticity is important according to the fashion trend of seeking comfort for clothing, and for interior building materials [8]. In addition, TPEEs have been receiving interest by industries as ecofriendly materials because they can save energy and reduce raw material and production costs due to their light weight [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many drawbacks in chemical forming. On one hand, the cell size of foam obtained with chemical foaming is usually dozens of micrometers . Liu prepared foams with 31–34 μm cell size from irradiation cross‐linked silicone rubber by using azodicarbonamide (AC) foaming agent .…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, the cell size of foam obtained with chemical foaming is usually dozens of micrometers. [5][6][7][8][9] Liu prepared foams with (2 of 11) 1600377 finalization. Size finalization can be achieved by cooling (thermoplastic material) or vulcanization (rubber).…”
Section: Introductionmentioning
confidence: 99%